Crime, unemployment, and xenophobia? An ecological analysis of right-wing election results in Hamburg, 1986-2005 - Ralph Rotte; Martin Steininger (Institute for the Study of Labor (IZA), 2008)
This paper investigates the consequences of immigration, crime and socio-economic depriviation for the performance of right-wing extremist and populist parties in the German city state of Hamburg between 1986 and 2005. The ecological determinants of voting for right-wing parties on the district level are compared to those for mainstream and other protest parties. Parallels and differences in spatial characteristics between right-wing extremist and populist parties' performance are identified. Our empirical results tend to confirm the general contextual sociological theory of right-wing radicalization by general social deprivation and immigration. Nevertheless they indicate that one has to be very cautious when interpreting the unemployment/crime - right-winger nexus. Moreover, crime does not seem to have a strong significant effect on right-wing populist parties' election successes despite its importance for their programmes and campaigns.
urn:nbn:de:101:1-20081126388
Keywords: D60; 330; Elections; political extremism; labor market policy; welfare policy; immigration; Wahlverhalten; Nationalistische Partei; Kriminalität; Ethnische Diskriminierung; Arbeitslosigkeit; Hamburg